WOMEN IN ISLAMIC FEMINIST VIEW - Imam Tabroni; Anita Nurul Wafa (SOKO GURU: Jurnal Ilmu Pendidikan, 2021)
This research article aims to examine women in Islamic studies who have occupied a very top position. Dialogical studies on women have been widely discussed by gender activists, especially discussions on gender equality. Among the feminist figures who advocate for women's rights and gender equality are Qasim Amin, Amina Wadud Muhsin, Fatimah Mernissi, and Asghar Ali Engineer. They look at women through their own thinking glasses. This paper only presents some of the opinions of these feminist figures, however, apart from the two opinions above, it is rarely mentioned that the presence of the Qur’an text on the theme of polygamy is a social response to the situation in pre- Islamic society, which tends to marry women in order to dominate. orphan properties. In addition, at that time polygamy was considered a symbol of prestige and social status, so it was not uncommon to find a tribal chief marrying many women and even tens or hundreds of them. Therefore, Islam actually comes with a message of social change to regulate unlimited polygamy, to restrictions and finally to monogamy; where women are no longer seen as property, but as equal partners to men. a more in-depth study there are still many thoughts of other Muslim feminist figures